2018
DOI: 10.1155/2018/7046927
|View full text |Cite
|
Sign up to set email alerts
|

Triphala Suppresses Growth and Migration of Human Gastric Carcinoma Cells In Vitro and in a Zebrafish Xenograft Model

Abstract: Objectives Triphala is an extensively prescribed traditional medicinal formula with potential therapeutic effects on various malignancies such as breast, colon, pancreas, prostate, ovarian, cervical, endometrial, and lymphatic cancer as well as melanoma. This study aimed to investigate Triphala for antitumor activities against gastric cancers. Methods In vitro tumor growth and migration of human gastric cancer cells were examined using the CCK-8 and Transwell assays, respectively. In vivo tumor progression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…It was also found that Triphala decreased the expression of phospho-Akt, phospho-p44/42, and phospho-NF-κB p56 in these gynecological cancer cells, which indicated that MAPK/ERK, PI3K/Akt/mTOR, and NF-κB/p53 signaling pathways were the possible mechanism of Triphala-induced apoptosis [60]. Besides its anti-proliferative and apoptotic effects, Triphala suppressed cell migration of cancer cells in vitro thus indicating its anti-metastatic potential [58].…”
Section: In Vitro Studiesmentioning
confidence: 75%
See 4 more Smart Citations
“…It was also found that Triphala decreased the expression of phospho-Akt, phospho-p44/42, and phospho-NF-κB p56 in these gynecological cancer cells, which indicated that MAPK/ERK, PI3K/Akt/mTOR, and NF-κB/p53 signaling pathways were the possible mechanism of Triphala-induced apoptosis [60]. Besides its anti-proliferative and apoptotic effects, Triphala suppressed cell migration of cancer cells in vitro thus indicating its anti-metastatic potential [58].…”
Section: In Vitro Studiesmentioning
confidence: 75%
“…[57] Inhibits gastric cancer cell proliferation and suppresses cell migration in vitro. [58] Exerts anti-proliferative, apoptotic and anti-migratory effects in colon cancer cells. [59] Inhibits proliferation of gynecological cancers cell with IC50 values of 98.28-101.23 µg/mL against SKOV-3, HeLa, and HEC-1B cells.…”
Section: Therapeuticmentioning
confidence: 99%
See 3 more Smart Citations